A Systematic Review of Population Monitoring Studies of Sea Turtles and Its Application to Conservation - Haley Hendrix; Sílvia Pérez-Espona (Diversity, 2024)
Sea turtles are keystone species in marine environments due to their essential role as seagrass grazers and population regulation of jellyfish and sponges in coral reefs. However, due to their predominant presence in coastal areas, sea turtle populations face significant threats due to the impact of human activities. In this systematic review, 655 peer-reviewed publications were analyzed to assess the extent of population monitoring for all seven sea turtle species. The analyses revealed that, although population monitoring studies have increased for sea turtles in the past four decades, these have been biased towards certain species and oceanic regions. Furthermore, sea turtle population monitoring has been undertaken primarily using field-based methods, with satellite tracking and nest surveys being the most commonly used methods; however, the implementation of genetic methods for population monitoring has increased since the 2000s. Direct conservation recommendations from this study include the urgent need to establish population monitoring studies in the Critically Endangered Kemp’s ridley and hawksbill and the Data Deficient flatback. Furthermore, population monitoring programs should be implemented in Southeast Asia and Northern and Central Africa, where knowledge on sea turtle populations is still limited. Finally, due to the long-distance movements of sea turtles, we also advocate for international cooperation and collaboration of local communities to protect these ecologically important and iconic marine species.